2007
DOI: 10.1111/j.1365-3180.2007.00533.x
|View full text |Cite
|
Sign up to set email alerts
|

Phalaris minor seedbank studies: longevity, seedling emergence and seed production as affected by tillage regime

Abstract: Studies were conducted to investigate seed longevity, seedling emergence and seed production of the weed Phalaris minor in wheat in northern India. The longevity of P. minor seeds buried in bags in the field was often limited to less than 1 year, although many seeds buried at 30 cm depth in a rice-wheat rotation remained viable for longer. The application of direct seeding in wheat reduced the seedling emergence rate of P. minor, when compared with conventional ploughing and sowing. However, a larger P. minor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 26 publications
1
45
0
Order By: Relevance
“…Under natural conditions, the seeds reach their highest germination percentage at 70 days after dispersal (Om et al, 2005). However, excess of soil humidity decreases their vigor and longevity, depending on their depth in the soil (Franke et al, 2007).…”
mentioning
confidence: 99%
“…Under natural conditions, the seeds reach their highest germination percentage at 70 days after dispersal (Om et al, 2005). However, excess of soil humidity decreases their vigor and longevity, depending on their depth in the soil (Franke et al, 2007).…”
mentioning
confidence: 99%
“…Additionally, when tillage intensity is reduced, more weed seeds remain on the soil surface and within the first few centimeters of the soil [46], making them more susceptible to seed predators [47,48] and seedling desiccation [49]. While the exact changes to the seedbank associated with tillage reduction in organic settings may be highly variable and difficult to quantify [38], results suggest that weed seedlings that emerge within no-till and reduced-tillage soils encounter greater resistance, and emerge at lower rates from the top layer of the soil profile [50], compared to tilled soils that allow deeper emergence [51]. Furthermore, weed seeds that germinate on the soil surface often experience fatal germination because the radicle may have difficulty penetrating the soil surface in a timely manner [38].…”
Section: Reducing Tillage Intensity In Organic Systems and Impacts Tomentioning
confidence: 99%
“…Mankowski et al (2013) reported that no-tillage reduced the number and weight of weeds compared to conventional cultivation with plowing. That could be explained by accumulation of seeds near the soil surface in no-tillage system, thus seeds are exposed to higher mortality risks through weather variability and predation (Blubaugh & Kaplan, 2015) and less seedling establishment (Franke et al, 2007).…”
Section: Effect Of Tillage Fertilization and Weed Control Treatmentsmentioning
confidence: 99%